Foreign Direct Investment and Environmental Challenges: A Case Study of Uganda With Analytical Perspective. - Byanyima, Faustino; Mayanja, Edison; Kadengye, Damazo T.; Arineitwe, Shine; Mijwil, Maad M.; Gaballa, Moustafa; Cherakkara, Veedu Rajeev; Turyasingura, Benson (Kabale University, 2024)
This chapter examines the connection between foreign direct investment (FDI) and environmental degradation in Uganda from 1990 to 2022. It includes control variables such as GDP growth, trade openness, urbanization, industrialization, and agricultural activity, utilizing data from the World Bank's World Development Indicators. Using the Autoregressive Distributed Lag (ARDL) model to tackle endogeneity, the study finds a significant long-term non-linear relationship between FDI and CO2 emissions, aligning with the Environmental Kuznets Curve (EKC) hypothesis. The results indicate an inverse U-shaped relationship, where carbon emissions initially increase with FDI before declining over time. The research highlights the influence of GDP growth, urbanization, agriculture, and industrialization on environmental outcomes. The findings stress the need for policymakers to balance attracting FDI with maintaining environmental sustainability, supporting the pollution haven theory in Uganda.